Conceptualising translational research in schools: A systematic literature review. (2022) - Jones, Sarah-Louise; Hall, Tony; Procter, Richard; Connolly, Cornelia; Fazlagić, Jan
Highlights: We conducted a systematic literature review on translational research in schools. Seventy-nine studies from twenty-five countries between 2010 and 2019 were coded and analysed. Five interlinked themes emerged from the data, deemed necessary for translational research to become a reality in education. An initial participatory framework of translational research in schools is proposed. Abstract: Since Stenhouse (1975) called for teachers to have ownership of research, there have been initial forays into teacher led research and evidence-based practice in schools. However, the notion of translational research in schools remains contested, in significant part because it still has not been rigorously conceptualised. This is an issue of increasing concern, in our rapidly developing world. Now, more than ever, we need research-informed education, to address the complex challenges faced by school communities, and those with the most significant role in supporting them: teachers. To address the gap in understanding how best to promote translational research in schools, this systematic literature review asked, what do innovative and impactful translational, teacher research infrastructures look like? By translational research, we mean a process of agentic and agonistic democracy within which teachers critically develop and, or use research to support their classroom practice. The purpose and focus of this paper therefore, is to present the current extent and form of translational research practices in schools by undertaking a comprehensive, systematic review of the published literature on the issue. We found that the potential for translational research in education can be considerably enhanced when five key themes are taken into consideration, these being: Teacher-Researcher Collaboration; Teachers as Researchers; Research Cultures in Schools; Teacher Agency; Sharing, Accessing and Utilizing Research. The notion of technology - as a theme in its own right - was notable by its absence. From the findings we have been able to propose a foundational framework of translational research in schools. To date there have been no other systematic literature reviews on translational research in education, nor any frameworks proposed; and thus this paper addresses a significant gap in the field.